Students' Regard on the Use of ChatGPT in their Writing Competence - Clezell Mae Obiso (FOSTER: Journal of English Language Teaching, 2024)
This qualitative case study explored the impact of ChatGPT on the writing competence of 3rd year BAEL students. It aimed to determine the use of ChatGPT on students' writing competency. A stratified purposive sampling method was used in selecting experienced participants. The scrutinized gathered data was subject to thematic analysis anchored by Braun and Clarke (2006), revealing both beneficial and counterproductive outcomes from using ChatGPT on students' writing competence. This concludes that the impact of ChatGPT on students’ writing was multifaceted highlighting the significance of adopting a well-rounded approach to maximize benefits and minimize potential drawbacks.